Comparison of Raman‐active crystals as a narrowband probe light source for picosecond three‐color vibrational CARS thermometry†. (11th April 2017) - Meißner, Christian; Tröger, Johannes W.; Kozlov, Dimitrii N.; Beyrau, Frank; Seeger, Thomas
Abstract : The feasibility of N2 ‐based vibrational three‐color coherent anti‐Stokes Raman scattering (CARS) thermometry employing narrowband stimulated Raman scattering (SRS) of a picosecond pump laser pulse in a Raman‐active crystal to provide the wavelength‐shifted probe radiation has been investigated. This shift of the probe beam wavelength is aimed to enable temperature measurements in sooting flames by using the established technique of N2 vibrational CARS spectroscopy in the range free from the interference of the detected radiation with the absorption/emission bands of the flame intermediate radicals C2 . The use of solid‐state Raman wavelength shifters may be an inexpensive solution providing reliable temperature measurements. The comparative study of the employment of two high SRS gain Raman‐active crystal materials [namely, Ba(NO3 )2 and KGd(WO4 )2 ] pumped by a 100‐ps frequency‐doubled Nd:YAG laser pulse has been performed. To test and compare the operation of each of the crystals in a three‐color CARS experiment, we have performed temperature measurements at ambient conditions and in a fuel‐rich sooting ethylene/air flame. Despite the comparable conversion efficiencies into the first‐order Stokes SRS radiation provided by both crystals, the achievable pulse energies were four to five times larger for the KGd(WO4 )2 crystal, and the vibrational CARS spectra at flame temperatures had a significantly better signal‐to‐noise ratio. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Solid‐state Raman shifters are for the first time tested and employed as a probe light source in a three‐color picosecond vibrational CARS approach for thermometry. The first results of temperature measurements under ambient conditions and in a sooting ethylene/air flame are presented. Therewith, temperature errors by N2 vibrational CARS measurements in sooting flames can be avoided.